Revisiting the optimized doping ratio in core/shell nanostructured upconversion particles. Issue 5 (18th January 2017) - Shen, Bin; Cheng, Shengming; Gu, Yuyang; Ni, Danrui; Gao, Yilin; Su, Qianqian; Feng, Wei; Li, Fuyou
Abstract : The development of rare-earth doped upconversion nanoparticles (RE-UCNPs) in various applications is fuelling the demand for nanoparticles with highly enhanced upconversion luminescence (UCL). Abstract : The development of rare-earth doped upconversion nanoparticles (RE-UCNPs) in various applications is fuelling the demand for nanoparticles with highly enhanced upconversion luminescence (UCL). Although the core/shell structure is proved to enhance the UCL effectively, there is still plenty of room to further improve the UCL by optimizing the doping ratio of the materials. In this article, a general strategy is demonstrated to achieve highly-enhanced visible UCL in core/shell nanostructured NaREF4 by increasing the doping ratio of Yb 3+ in the core region. The energy transfer from RE-UCNPs to surface quenching sites through Yb 3+ –Yb 3+ energy migration is demonstrated to be the main reason for restricting the doping ratio of Yb 3+ . Notable UCL enhancement ( ca. 15 times) of core/shell structured α-NaYF4 :Yb, Er@CaF2 nanoparticles is observed by increasing the concentration of Yb 3+ to 98 mol%. The highly-enhanced visible UCL signal is used to guide the lymphatic vessel resection with the naked eye.